Temperature management during cytoreductive surgery with hyperthermic intraperitoneal chemotherapy - Ramirez, Maria F.; Guerra-Londono, Juan Jose; Owusu-Agyemang, Pascal; Fournier, Keith; Guerra-Londono, Carlos E. (Frontiers in Oncology, 2023)
In addition to attaining complete or near complete cytoreduction, the instillation of select heated chemotherapeutic agents into the abdominal cavity has offered a chance for cure or longer survival inpatients with peritoneal surface malignancies. While the heating of chemotherapeutic agents enhances cytotoxicity, the resulting systemic hyperthermia has been associated with an increased risk of severe hyperthermia and its associated complications. Factors that have been associated with an increased risk of severe hyperthermia include intraoperative blood transfusions and longer perfusion duration. However, the development of severe hyperthermia still remains largely unpredictable. Thus, at several institutions, cooling protocols are employed during cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS-HIPEC). Cooling protocols for CRS-HIPEC are not standardized and may be associated with episodes of severe hyperthermia or alternatively hypothermia. In theory, excessive cooling could result in a decreased effectiveness of the intraperitoneal chemotherapeutic agents. This presumption has been supported by a recent study of 214 adults undergoing CRS-HIPEC, where failure to attain a temperature of 38◦ C at the end of chemo-perfusion was associated with worse survival. Although not statistically significant, failure to maintain a temperature of 38◦ C for at least 30 minutes was associated with worse survival. Although studies are limited in this regard, the importance of maintaining a steady state of temperature during the hyperthermic phase of intraperitoneal chemotherapy administration cannot be disregarded. The following article describes the processes and physiological mechanisms responsible for hyperthermia during CRS-HIPEC. The challenges associated with temperature management during CRS-HIPEC and methods to avoid severe hypothermia and hyperthermia are also described